Negotiating cultural hybridity through Marvel`s Kamala Khan: reading the secret superhero identity "Ms. Marvel" as a third space - Cicholewski, Alena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In October 2014 the first issue of a new "Ms. Marvel" comic book series starring Muslim Pakistani American teenager Kamala Khan was published and was met with both critical acclaim and commercial success. In the ongoing series, Muslim Pakistani American teenager Kamala Khan struggles to come to terms with the expectations of her Pakistani parents and her desire to fit into mainstream American society.
Keywords: hybridity; identity politics; postcolonial theory; superhero comics; Third Space